Effects of groundwater pumping for irrigation on stream properties of the Arikaree River on the Colorado plains - Fardal, Lisa L., author; Burke, Ingrid C., advisor; Bledsoe, Brian P., committee member; Oad, Ramchand Naraindas, committee member (Colorado State University. Libraries, 2003)
The Arikaree River lies in the Republican River Basin on the Northern High Plains of Colorado. This study was conducted on the portion of the Arikaree River that flows through the lower portion of Yuma County, Colorado. A groundwater dependent stream, it obtains its flow from springs and seeps. Discharge into the stream channel occurs wherever the aquifer head is higher than the elevation of the river bottom. On this river, there is a state-threatened species of minnow that is reportedly suffering due to lack of seasonal flow. It is assumed that groundwater pumping for irrigation is reducing the quantity of water within this river. However, the stream/aquifer relationships in this area are not well understood. Farmers in this area irrigate crops such as corn and alfalfa with groundwater that is pumped from the High Plains, or Ogallala aquifer. During the summer of 2002, the area experienced a severe drought that required farmers to irrigate continuously throughout the season. A mere 7.6 centimeters of precipitation fell on the land to supplement the irrigation water. The irrigation practices of six representative farmers within the area were analyzed. Several parameters including the crop type and area, well pumping rates and duration of irrigation and evapotranspiration rates of the crops were examined for each field. The results show that a large quantity of water is withdrawn from the aquifer for irrigation purposes; however, most farmers were found to be in deficit irrigation for the majority of the 2002 season. This study also observed the status of the river during the season. Stage height and connectivity of the river were recorded throughout the season. The volume of water extracted from the aquifer for irrigation purposes appears to have had a definite impact on the stage height and connectivity of the nearby Arikaree River. As groundwater pumping for irrigation increased, the stage height of the river decreased. Likewise, as the pumping concluded in the fall season, the water level of the river increased. While there are likely to be several factors influencing stage height of a stream, irrigation seems to be a major influence. A more accurate description of the groundwater hydrology and the surface/groundwater relationship of this area is necessary to verify this correlation and to make robust management suggestions to the irrigators in this area. Future research may entail more detailed descriptions of the river hydraulics, groundwater studies for stream/aquifer relationships, and modeling groundwater table depletions in conjunction with irrigation withdrawal.
Keywords: Irrigation -- Environmental aspects -- Colorado -- Yuma County; Groundwater flow -- Colorado -- Yuma County